Describing the administrative border of Koshtepa district on an electronic digital map and creating a web map - Eshnazarov, Doniyor; Abdukadirova, Mukharram; Abdurakhmonov, Abdukhokim; Yokubov, Sherzodbek (E3S web of conferences, 2023)
In this article, the administrative border of the district is described on an electronic digital map and a web map is created, on the basis of the obtained results, in the development of target state programs for the establishment of digital maps connected to coordinate systems in the determination of the boundaries of villages and towns of the Koshtepa district of Fergana region and the determination of the boundaries of administrative-territorial units, and the design and determination of administrative boundaries data is provided.